DETERMINANTS AND STRUCTURAL DIMENSIONS OF THE ATTRACTIVENESS OF IDEOLOGICAL AND POLITICAL COURSES AMONG MEDICAL STUDENTS - Zhang, Yu; Cai, Yonghong; Wu, Xiaowei; Han, Yingxiong; Deng, Lei; Hu, Hang (Chinese Journal of Social Science and Management, 2026)
Purpose: Enhancing the appeal of ideological and political courses is pivotal for strengthening the effectiveness of ideological and political work in universities and ensuring long-term social stability. Focusing on the specific cohort of medical and pharmaceutical students, this study aims to systematically investigate the constituent elements and internal structure of the appeal of these courses and to develop a standardized measurement tool. Study Design/Methodology/Approach: A mixed-methods research design was employed. First, in-depth interviews were conducted with 26 medical and pharmaceutical students, and text analysis was used to extract the core elements and construct a preliminary theoretical model. Subsequently, a measurement scale was developed based on the interview findings. A survey was then administered to 500 students, and Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were performed using SPSS 27.0 and AMOS 24.0 to test the reliability and validity of the instrument. Findings: The results indicate that the appeal of ideological and political courses for medical and pharmaceutical students comprises four dimensions: Value-driven Force, Cognitive Constructive Force, Situational Embeddedness Force, and Teaching Supportive Force. Empirical evidence showed that the Cronbach’s alpha coefficient of the scale was 0.981, and all fit indices met the requirements of psychometrics. Originality/Value: Data analysis further revealed that medical and pharmaceutical students place significantly higher importance on the dimension of Cognitive Constructive Force. The instrument developed in this study demonstrates high reliability and provides a scientific basis and practical reference for medical colleges to accurately evaluate and optimize the quality of ideological and political teaching.